Class and Gender Emergences in Elena Aldunate Bezanilla S "Juana y la Cibernética": Machines and Desiring Female Workers - Contreras-Candia, L (PONTIFICIA UNIV CATOLICA CHILE, FAC LETRAS, 2025)
This article addresses the cultural and aesthetic tensions developed in Chilean writer Elena Aldunate Bezanilla s narration "Juana y la cibern & eacute;tica". Following the main character s vital itinerary, I trace the insubordinations undertaken against the sex/ gender system and the disobedience to the writing precepts displayed in this narration. The fictional universe articulated in this text operationalizes creative freedom mechanisms and interrupts the dominant symbolic orders. In addition, I establish some connections between feminism s theoretical lineaments, the figure of young southern cone researchers and Aldunate s short story, because we believe that we can identify some coincidences.